Talpa: Los caminos de la luna - Victor Manuel Cárdenas (Estudios sobre las Culturas Contemporáneas)
In this chronicle of the annual pilgrimage to Talpa, the author gives a literary description of distinct moments and facets of a deeprooted popular cultural and religious practice: "mandas" (promises made to the Virgin in return for personal favors) and the pilgrimage to the sanctuary of the Virgin of Talpa.